2016
DOI: 10.4238/gmr.15018078
|View full text |Cite
|
Sign up to set email alerts
|

Sperm quality and DNA damage in men from Jilin Province, China, who are occupationally exposed to ionizing radiation

Abstract: ABSTRACT. Long-term radiation exposure affects human health. Ionizing radiation has long been known to raise the risk of cancer. In addition to high doses of radiation, low-dose ionizing radiation might increase the risk of cardiovascular disease, lens opacity, and some other non-cancerous diseases. Low-and high-dose exposures to ionizing radiation elicit different signaling events at the molecular level, and may involve different response mechanisms. The health risks arising from exposure to low doses of ioni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 33 publications
1
24
0
2
Order By: Relevance
“…Such a group is the staff of X-ray laboratories. Among males exposed to contact with radioactivity, a decrease was observed in sperm motility, an increase in the percentage of pathological sperm (the abnormalities concerned primarily the head), as well as an intensification of vacuolization [51,52]. In addition, examinations of the genetic material in the sperm of these males showed an intensification of fragmentation and total methylation of genomic DNA [51].…”
Section: Conditioning Of Radiosensitivity Of Premeiotic Cells Cells mentioning
confidence: 98%
“…Such a group is the staff of X-ray laboratories. Among males exposed to contact with radioactivity, a decrease was observed in sperm motility, an increase in the percentage of pathological sperm (the abnormalities concerned primarily the head), as well as an intensification of vacuolization [51,52]. In addition, examinations of the genetic material in the sperm of these males showed an intensification of fragmentation and total methylation of genomic DNA [51].…”
Section: Conditioning Of Radiosensitivity Of Premeiotic Cells Cells mentioning
confidence: 98%
“…The testis, as one of the most radiation sensitive organs, can be significantly impaired by even low doses of radiation [8]. The reported dysfunctions include sperm chromosome aberrations [9], motility decreased [10], swimming behavior impaired [11] and testis weights decreased [12]. Spermatogenesis is a complex process involving a wide series of cellular events, ranging from spermatogonia, spermatocytes, spermatids and spermatozoa [13, 14].…”
Section: Introductionmentioning
confidence: 99%
“…In 2013, a study of 83 occupationally exposed health workers clarified the effects in spermatozoa which showed changes in motility characteristics, increased sperm morphological abnormalities, sperm DNA fragmentation and global hyper methylation (Kumar et al 2013). A subsequent study also showed decreased sperm motility, abnormal morphology and significantly higher DNA fragmentation index in exposed compared to non-exposed men (Zhou et al 2016). These studies provide new insights into low-dose risks on human sperm characteristics but are limited by the small sample size in each case.…”
Section: Occupational Irradiationmentioning
confidence: 99%